The in vitro effect of nebulised hypertonic saline on human bronchial epithelium. Issue 5 (17th May 2018) - Goralski, Jennifer L.; Wu, Dan; Thelin, William R.; Boucher, Richard C.; Button, Brian
Inhaled hypertonic saline (HS) is an effective therapy for muco-obstructive lung diseases. However, the mechanism of action and principles pertinent to HS administration remain unclear. An in vitro system aerosolised HS to epithelial cells at rates comparable to in vivo conditions. Airway surface liquid (ASL) volume and cell height responses were measured by confocal microscopy under normal and hyperconcentrated mucus states. Aerosolised HS produced a rapid increase in ASL height and decrease in cell height. Added ASL volume was quickly reabsorbed following termination of nebulisation, although cell height did not recover within the same time frame. ASL volume responses to repeated HS administrations were blunted, but could be restored by a hypotonic saline bolus interposed between HS administrations. HS-induced ASL hydration was prolonged with hyperconcentrated mucus on the airway surface, with more modest reductions in cell volume. Aerosolised HS produced osmotically induced increases in ASL height that were limited by active sodium absorption and cell volume-induced reductions in cell water permeability. Mucus on airway surfaces prolonged the effect of HS via mucus-dependent osmotic forces, suggesting that the duration of action of HS is increased in patients with hyperconcentrated mucus. This study provides insight into the magnitude of effect of hypertonic saline on airway surface hydration in muco-obstructed diseases http://ow.ly/FAVd30iR9Bj